Tunable PEG Hydrogels for Discerning Differential Tumor Cell Response to Biomechanical Cues. Issue 12 (22nd August 2022) - Katz, Rachel R.; West, Jennifer L.
Abstract: Increased extracellular matrix (ECM) density in the tumor microenvironment has been shown to influence aspects of tumor progression such as proliferation and invasion. Increased matrix density means cells experience not only increased mechanical properties, but also a higher density of bioactive sites. Traditional in vitro ECM models like Matrigel and collagen do not allow these properties to be investigated independently. In this work, a poly(ethylene glycol)‐based scaffold is used which modifies with integrin‐binding sites for cell attachment and matrix metalloproteinase 2 and 9 sensitive sites for enzyme‐mediated degradation. The polymer backbone density and binding site concentration are independently tuned and the effect each of these properties and their interaction have on the proliferation, invasion, and focal complex formation of two different tumor cell lines is evaluated. It is seen that the cell line of epithelial origin (Hs 578T, triple negative breast cancer) proliferates more, invades less, and forms more mature focal complexes in response to an increase in matrix adhesion sites. Conversely, the cell line of mesenchymal origin (HT1080, fibrosarcoma) proliferates more in 2D culture but less in 3D culture, invades less, and forms more mature focal complexes in response to an increase in matrix stiffness. Abstract : The stiffness and adhesivity of poly(ethylene glycol) hydrogels influence the behavior of tumor cells cultured within or on top of these hydrogels. A triple negative breast cancer cell line is shown to primarily respond to the adhesion ligand concentration while a fibrosarcoma cell line is shown to primarily respond to the stiffness of these hydrogels.